Korupsi Kecil Pada Layanan Keagamaan Direktorat Jenderal Bimbingan Masyarakat Buddha - Dian Hafit Syaifullah (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
The Directorate General of Buddhist Community Guidance (Ditjen Bimas Buddha) has carried out a bureaucratic reform program since 2012 intending to become a work unit with a predicate Free Area from Corruption. The unfolding of the grand corruption case involving top officials in the project to procure religious education books raises whether the same corruption also occurs in religious services for the Buddhist community. This research aims to uncover the petty corruption levels in religious services and the factors contributing to these outcomes. This research uses a mixed-method approach with a sequential explanatory research design that applies surveys and qualitative methods to explain the survey achievements with GONE theory analysis from Bologna. This study's findings are the value of the corruption behavior of religious services at the Directorate General of Bimas Buddha exceeds the minimum score of 13.5 to get the predicate of a corruption-free area. The level of petty corruption in religious services is deficient, thus meeting a Corruption Free Zone's requirements. The factors that contribute to this achievement are the fulfillment of the basic needs of service officers by institutions, the low greed of officers due to pujabakti activities initiated by service officers personally, the reduced opportunities for corruption with the implementation of e-government (Organization Information System applications and Houses of Worship.